Evaluación físico - sensorial de tres tipos de pollos ahumados bajo el efecto de tres niveles de jengibre, en el cantón y provincia de Santo Domingo de los Tsáchilas - Hailla Zapata, Hernan Heriberto (2014)
Presently study was investigated the influence in three cooking ways in the sensorial and economic characteristics of smoky chickens under four levels of ginger like preservative, the studied variables were: characteristic Yield of the chicken%, Color of the smoky chickens, Flavor of the smoky chickens, Texture of the smoky chickens, Catación of the smoky chickens, Time of life at shelf level, production Costs, dollars/kg, Profitability, Benefice/cost. As for yield of the chicken in percentage on the average for treatment were T1 67,166, T2 64,065, T3 60,714, T4 63,609, T5 75,536, T6 67,226T7 68,704, T8 71,41, T9 84,568 T10, 79,664 T11 79,769, T12 78,901. Compared the yields to each other, it constitutes that of more yield the treatment 11, continued by the treatment 10, that of smaller yield constituted the treatment 3. The best puntajes in color of the smoky chickens reached those cooked in dry at 75°C., the sumatoria averages of the group they reached at 112,80, have more than enough 120 possible As for the flavor the chickens better accepted they were those cooked in dry and they accumulated 107,70 points on the whole on 120 possible, continued by the smoky chickens that were cooked to vapor until arriving to an internal temperature of the coldest point in 40 ° C with 102,30 points. As for catación the chickens better accepted by the appraisers they were those cooked in dry and they accumulated 107,60 points of 120 on the whole possible, continued by the smoky chickens that were cooked to vapor until arriving to an internal temperature of the coldest point in 40 ° C with 103,10 points of 120 possible and in third place the cooking system was located to vapor until arriving to an internal temperature of the coldest point in 60 ° C with 97,95 points of 120 possible. In time of life the smoky chickens evaluated at block level, in accumulated time gave better results those that were coccids in dry, with 227 accumulated days of a foreseen time of 240 days. In production costs in total ascends to $736,847 dollars, the treatment that bigger expenditure tube was the T1, with $62,39, while the treatment T 8, I spend fewer whose value was of $59,19 dollars. The profitability in percentage of the chickens smoked by treatment was the following ones: T1% 26,37; T2% 6.55; T3% - 2,63; T4% - 3,01; T5% 41,73; T6% 13,47; T7% 9,87; T8% 8,63; T9% 61,88; T10% 36,65; T11% 29,49 and T12 %22,17. The last four treatments have better profitability, while the treatments T3 and T4 don't have profitability.